Arsenic Distribution and Speciation in Antigorite-Rich Rocks from Vermont, USA - Niu, Lijie (Université d'Ottawa / University of Ottawa, 2011)
Summary Serpentinites from the northern Vermont were examined for the distribution and abundance of As. XRD and electron microprobe showed the samples are composed of antigorite, chromite, magnetite, and carbonate minerals (magnesite, dolomite, calcite). The concentration in As when the samples were dissolved in H3PO4 was 10% of the concentration in As when the samples were dissolved in concentrated HF/HNO3, suggesting that As is mainly incorporated in the structure of antigorite. X-ray absorption near-edge structure spectra showed that the As is As(III) in the samples. Extended X-ray absorption fine structure spectra suggested that the As has a tetrahedral coordination and is located in the Si-site in serpentine.
Keywords: Arsenic; X-ray absorption near-edge structure; XRD; Extended X-ray absorption fine structure; electron microprobe; acid leaching; diffusion; pH